Legal Counseling on Fast Procedural Law for Business and Investment in the Public Dialogue on the Draft Civil Procedure Law - Iriawan, Asep Iwan; Nurbaiti, Siti; Permanasari, Arlina; Jamal, Carissa Belia Putri (AIWADTHU: Jurnal Pengabdian Hukum, 2025)
Introduction: National economic growth requires a responsive and efficient legal system, particularly in the field of business and investment. The Draft Bill on Civil Procedure Law is expected to provide legal certainty and accelerate the resolution of business and investment disputes.Purposes of The Devotion: This article aims to provide understanding of fast-track civil procedure for business and investment through public dialogue.Method of The Devotion: The method applied was lecture and interactive discussion, using an empirical approach based on stakeholder participation in public dialogue.Results Main Findings of the Devotion: The community service activity revealed that participants gained broader knowledge of business dispute resolution through both litigation and non-litigation, fast-track proceedings in civil procedure law, and academic aspects of the Draft Bill. The enthusiasm of the participants highlighted the urgent demand for a faster and more efficient civil procedure system. These findings emphasize the importance of reforming civil procedural law to foster a favorable investment climate and ensure legal protection for business actors.